A retrospective comparison of ketamine dosing regimens for pediatric procedural sedation. (April 2015) - Heilbrunn, Benjamin R.; Chang, Todd P.; Liu, Deborah R.
<x xml:space="preserve">Abstract</x> Objective Ketamine is a dissociative agent often used in pediatric emergency departments for procedural sedation. Institutions commonly use either 1.5 mg/kg (k1.5) or 1 mg/kg (k1.0) as intravenous dosing. We sought to determine whether patients receiving k1.0 require more administered doses during sedation than patients receiving k1.5. Furthermore, we examined whether differences existed between k1.0 and k1.5 in the total dosage, total mg/kg, and time to recovery. Patients and methods A retrospective chart review examining procedural sedations from July 2010 through December 2011 was performed for sedations using k1.0 or k1.5. Cohorts were compared on the basis of the number of doses, mg/kg administered, total dosage (mg), and adverse events. Results A total of 346 patients were included, with 159 patients in k1.0 and 187 patients in k1.5. No significant differences in demographics were observed between k1.0 and k1.5. Patients in k1.5 required fewer median doses of ketamine compared with k1.0 (1.0 vs. 2.0, P=0.02). k1.0 had a higher median overall mg/kg dosage (1.71 mg/kg) than k1.5 (1.60 mg/kg) (P<0.01). k1.5 showed a decrease in the number of sedations requiring a third dose of ketamine to complete sedation as compared with k1.0 (7.57 vs. 18.47%, P=0.002). No significant difference in adverse events was found between k1.0 and k1.5. Conclusion Sedations using k1.5 require fewer doses, lower mg/kg administered, but a higher total dose than k1.0. No difference was found in the rate of adverse events between the groups. Our findings suggest that ketamine sedations can be completed safely with one dose when patients are initially dosed at 1.5 mg/kg.